Towards inclusion of all learners through science teacher education - Koomen, Michele (Studies in inclusive education (Sense Publishers), 2018)
Towards Inclusion of All Learners through Science Teacher Education serves as an indispensable resource for teachers and teacher educators wishing to understand how to educate students with exceptionalities in science. This book begins with the voices and stories of the experts: current and former K-12 students with disabilities sharing their experiences in science education classrooms. The voices of students with disabilities are then connected to the work of leading experts in the area of science education for individuals with disabilities in an effort to address the goals of national reform documents by ensuring rigorous science experiences for all students. It is written in a highly accessible and practical manner, making it ideal for all educators including pre-service and in-service teachers, teacher educators, researchers, and curriculum developers.